Correction: Can aromaticity be a kinetic trap? Example of mechanically interlocked aromatic [2-5]catenanes built from cyclo[18]carbon. Issue 28 (27th March 2020) - Fedik, Nikita; Kulichenko, Maksim; Steglenko, Dmitriy; Boldyrev, Alexander I.
Abstract : Correction for 'Can aromaticity be a kinetic trap? Example of mechanically interlocked aromatic [2-5]catenanes built from cyclo[18]carbon' by Nikita Fedik et al., Chem. Commun., 2020, 56, 2711–2714.